Use the form y=mx +b for linear equations. Write the equation for the following relation. C = {(x, y): (6, 15), (8, 21), (10, 27),}

I’m not sure if the answer is right, but here you go.

y=mx+b 

’m’ is for gradient of the line. First, calculate the gradient.

Let’s use (6,15) and (8,21)

Gradient, m = \( y_{2} \) - \( y_{1} \)
                    -
                     \( x_{2} \) - \( x_{1} \)
                 
                 =  21 - 15     = 6       = 3
                     -   
                       8 - 6         2
           
Therefore, m = 3. Now let’s search ’b’.
Let’s use (6,15) again. Substitute it into the equation.

y=mx+b 
15 = 3 (6) + b
b = -3

Thus, the equation : y=3x -3 




RELATED: